Axiological Ethics of F. Brentano and of G. E. Moore: A Comparision - Norkus, Zenonas (Problemos, 1991)
Meta-ethics, axiology and (partly) normative ethics of British philosopher G. E. Moore (1873-1958) and those of Austrian philosopher F. Brentano (1838- 1917) are compared. While G. E. Moore treated “intrinsic good” (the basic concept of axiological ethics) as indefinable, F. Brentano proposed the original non-naturalistic “epistemic” definition of the concept. This definition is compatible with different conceptions concerning the ontological nature of the object of “intrinsic good”. Normative ethics of both philosophers is qualified as pluralistic conservative act utilitarianism.